Renewable & Non-Renewable Energy Sources in India: A Study on Future Prospects - Dr. Sunita Pachar (International Journal of Advanced Science and Technology, 2020)
In worldwide energy sector is witnessing a continuing changeover from traditional energy sources like coal or petroleum to clean energy sources like solar, thermal energy or ocean energy. India’s energy strategies observe the country’s accomplishment in raising its energy sector as well as the challenges it faces in ensuring a sustainable energy future. In future Green energy and RE can provide many employment opportunities in India. India has a huge potential in green energy and by its use people life standard can be enhanced. This paper talks about future prospects of renewable energy in India. There are huge possibilities of green energy in India. Indian Government Ministry of New and Renewable Energy Sources (MNRE) are working on some large and effective projects to make Green energy successful in India. Ministry is working to grow electricity production almost double until 2022.Nowdays pollution is biggest issue which every developing and developed country is facing. By using green or Renewable energy (RE) industrial organizations can minimize environment pollution. Green energy or RE main advantage is that these energy Sources are Sustainable which are easily available everywhere in India. Green energy Scope is worldwide.